EFFECTIVE MARKETING TRAINING FOR MSMES WITH THE CONCEPT OF TECHNOPRENEUR - Wirasmara Kusuma, Hero; Azizi, Enji (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Even though the number of MSMEs in Indonesia continues to increase while bringing many positive effects in the form of employment which can reduce unemployment and others, problems with MSMEs or Micro, Small, and Medium Enterprises do often occur. The problem that most often occurs lies in marketing, which turns out to be a lot of people who don't understand online marketing. Even though many MSME actors market their products through marketplace sites, social media accounts, and so on, they are not optimal and consistent in practice. Therefore, we introduce the concept of Marketing 4.0 which redefines marketing from Marketing 3.0, namely marketing must adapt to the changing nature of the customer path in the digital economy, where the role of marketers is to guide customers along their journey from awareness and finally to advocacy. It is the concept that we are trying to socialize to MSMEs in carrying out effective marketing techniques for their businesses, of course with the technopreneur concept which they have been used to doing so far. In this training, marketing strategies for MSME products, as well as MSME marketing strategies, are explained, from the marketing strategies commonly used in the form of; creating unique products, marketing products by becoming a networker, determining STP, and taking advantage of e-commerce. Next, we describe a marketing strategy that 1. embraces the shift to a more horizontal, inclusive, and social business landscape, 2. explains the changing landscape creates a series of paradoxes that marketers have to face, one of which is online versus offline interaction, 3. Understands that young people are sharing thoughts, women for market share, and netizens for sharing hearts, 5. Inviting MSME businesses to redefine marketing in the digital economy, as well as develop a new framework for marketing in the digital economy.